Upaya Meningkatkan Kesehatan Warga Di Kecamatan Mangarabombang Melalui Penyuluhan Kesehatan Penyakit Kanker Payudara Dan Rahim - Sul Jalali Sukuri; Muthiaturrahma Syaifuddin (PPM LP2M UIN Alauddin Makassar, 2022)
Efforts to improve health, especially for breast cancer and uterine cancer in women. Breast cancer is the highest cause of death for women in Indonesia. This is because breast cancer sufferers go to health services when breast cancer is at an advanced stage. The delay in treatment was due to a lack of public knowledge about breast cancer and the lack of knowledge on how to do breast self-examination (BSE) for early detection of breast cancer. Handling breast cancer from an early stage is expected to reduce mortality and increase life expectancy (Erlina, 021). In addition, uterine cancer is the second most common type of cancer suffered by women worldwide, usually affecting women aged 35-55 years. There are 70,000 women in the world diagnosed with cervical cancer every year and 85% are in developing countries including Indonesia (Monica, 017). The results of the activity show the usefulness and increased understanding of the residents represented by PKK women, which are expected to be able to disseminate information on this counseling. God willing, this counseling activity can be an effort to improve the health of local residents.Keywords: Service, Counseling, and Cancer